Utilization of bagasse ash in high-strength concrete - Rukzon, Sumrerng; Chindaprasirt, Prinya (Materials in engineering, 2012)
► The incorporation of BA up to 30% replacement level increased the resistance to chloride penetration. ► The use of 10% of BA produced concretes with good strength and low porosity. ► Reasonably, the substitution of 30% BA is acceptable for producing high-strength concrete. This paper presents the use of bagasse ash (BA) as a pozzolanic material for producing high-strength concrete. Portland cement type I (PC) is partially replaced with finely ground bagasse ash. The concrete mixtures, in part, are replaced with 10%, 20% and 30% of BA respectively. In addition, the compressive strength, the porosity, the coefficient of water absorption, the rapid chloride penetration and the chloride diffusion of concretes are determined. The test results indicate that the incorporation of BA up to 30% replacement level increases the resistance to chloride penetration. Besides, the use of 10% of BA produced concretes with good strength and low porosity. Reasonably, the substitution of 30% BA is acceptable for producing high-strength concrete.